Stochastic-Based Models for Electricity Market Analysis with High Wind Energy Penetration - Martín-Rivas, Sebastián (Universidad de Málaga, Servicio de Publicaciones y Divulgación Científica, 2014)
Renewable energy is now seen as an almost indispensable instrument to overcome or at least mitigate climate change. Wind and solar energy are among the most generally quoted renewable energy forms that are envisaged to offer the quantitative potential contribution to decarbonization, and between them, wind energy is the one usually considered to be closest to being economic. A system of incentives has been, and remains, necessary to foster the development of intermittent sources with the view of increasing their penetration into generation systems, sometimes at levels that are unjustified by current market conditions. The effects of incentive policies of the subsidy type are usually difficult to monitor, and unintended consequences should not come as a surprise. This is the case in the European Union, which has been at the forefront of the use of renewable energy with the result that subsidized intermittent capacities are now jeopardizing the short term economics of conventional units to a level that puts the adequacy of the system in question, with many new conventional plants being mothballed or dismantled because they are not profitable. This thesis concentrates on the situation going on in some European countries, where the high penetration of renewable energy, combined with energy conservation and other events related to the economic crisis have lead to a reduction of wholesale electricity prices that questions the survival of conventional plants in the market. The main questions addressed are the loss of conventional assets value, the cost of the subsidies implied by the current policies, and the influence of the technical constraints (reserve, ramping constraints and uncertainty in wind generation) for the system operation. The methodology consist of using equilibrium models based on stochastic programming. Two kinds of models are considered: i) a complementarity formulation for a multi-firm configuration that accounts for the separation between the PX and the TSO, and ii) a welfare maximization problem for a single firm configuration. All the models assume price taking agents and no market power with the objective to simplify the economic discussion and concentrate on the economic and physical issues of market design. The use of the models is illustrated on two questions motivated by the current phenomena observed in Europe, that consist of conventional plants, necessary for providing services, are driven out of the market because of low energy prices. The common wisdom (and the observation of the market) is that renewable energies induce a decrease of energy prices together with a reduction of the activity, and the profit, of the conventional units. The models show that this phenomenon indeed seems rather stable under different structural assumptions (premium to wind generation and risk aversion), but it may also crucially depend on the demand for ancillary services (here frequency maintenance) induced by renewable energies and on their pricing by the market design. We find that a higher demand for load following reserve and an economically sound pricing (marginal cost pricing) restore the revenue of the conventional plants. The question of the sustainability of conventional plants then leads to the proper identification of the demand for services and the acceptance that they will be properly remunerated.
Keywords: Energía eléctrica - Producción; Programación estocástica; Electricity market; Stochastic programming; Wind generation